Vanished in the night - Eason, Lynette (Eason, Lynette. Wrangler's corner., 2018)
After saving Kaylee Martin from abduction and delivering her baby boy on the side of the road, Dr. Joshua Crawford can't get them out of his mind. Unfortunately, neither can Kaylee's violent stalker. He'll stop at nothing to get to the new mom and her child. Can Joshua keep them safe so they can become the family he's dreamed about?